Evaluation of pathogenicity islands in uropathogenic Escherichia coli isolated from patients with urinary catheters - Farzaneh Firoozeh; Leila Soleimani-Moorchekhorti; Mohammad Zibaei (Journal of Infection in Developing Countries)
Introduction: Uropathogenic Escherichia coli (UPEC), an important causative agent of urinary tract infections (UTIs), carries virulence factors which are clustered on pathogenicity islands (PAIs). The goal of this study was to characterize the PAIs among the UPEC isolated from patients with urinary catheters.